دراسة كفاءة وسائل الاختبار باستخدام طريقة Cg/Cgk و طريقةGRR . - انتصار برهوم (Tishreen University, 2019)
The laboratories located in the scientific, industrial and inter-disciplinary institutions are of great importance. They always strive to produce accurate and accurate results and to prove the accuracy of their results and to monitor the quality of the product so that these products comply with the standards set, Production and quality, the lack of full implementation of quality systems within laboratories is one of the main reasons for obtaining inaccurate results.This study presents a study on the efficiency of the means of testing using quality testing methods and tools to determine whether the test method is valid for a particular test function. The product quality is determined by the test method. The efficiency of the testing process is determined by examining the efficiency of the testing and measurement processes and analyzing the measurement systems according to standard methods, including the Cg / Cgk method and the GRR method.                                                                                    إن المختبرات القائمة في المؤسسات العلمية والصناعية والبينية لها أهمية كبرى ، فهي تسعى دائما لإعطاء نتائج صحيحة و دقيقة ،وإلى إثبات مستوى الدقة التي تتميز بها نتائجها، كما أنها تعمل على مراقبة جودة المنتج بحيث تتوافق هذه المنتجات مع المواصفات القياسية الموضوعة ، مما يؤدي إلى تطوير تقنيات الإنتاج والجودة ، فعدم التطبيق الكامل لأنظمة الجودة داخل المختبرات يعد من أهم الأسباب التي تؤدي للحصول على نتائج غير دقيقة. يقدم هذا البحث دراسة فيما يخص كفاءة وسائل الاختبار باستخدام طرائق و أدوات اختبار الجودة ، بحيث تعطي قراراً فيما إذا كانت وسيلة الاختبار صالحة من أجل وظيفة اختبار معينة ، فجودة المنتج تتحدد بشكل مقرر من خلال وسيلة الاختبار. ويتم تحديد كفاءة عملية الاختبار من خلال دراسة كفاءة عمليات الاختبار والقياس وتحليل أنظمة القياس وفق طرق معيارية منها طريقة Cg/Cgk و طريقةGRR .